2010
DOI: 10.1186/1471-230x-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of liver fibrosis and risk factors in a general population using non-invasive biomarkers (FibroTest)

Abstract: BackgroundFibroTest and elastography have been validated as biomarkers of liver fibrosis in the most frequent chronic liver diseases and in the fibrosis screening of patients with diabetes. One challenge was to use them for estimating the prevalence of fibrosis, identifying independent risk factors and to propose screening strategies in the general population.MethodsWe prospectively studied 7,463 consecutive subjects aged 40 years or older. Subjects with presumed advanced fibrosis (FibroTest greater than 0.48)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(162 citation statements)
references
References 32 publications
12
143
2
5
Order By: Relevance
“…This incidence is higher than the 10% incidence observed in Asian young adults with NASH or 14.4 % (septal/bridging fibrosis combined) in NAFLD patients, as assessed by histopathology (Gramlich et al, 2004;Tsang et al, 2006). It is also markedly higher than the 2.8% bridging fibrosis reported in French young adults or 6% in European young adult HCV patients coinfected with HIV, as estimated by FibroTest V R (Martín-Carbonero et al, 2009;Poynard et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…This incidence is higher than the 10% incidence observed in Asian young adults with NASH or 14.4 % (septal/bridging fibrosis combined) in NAFLD patients, as assessed by histopathology (Gramlich et al, 2004;Tsang et al, 2006). It is also markedly higher than the 2.8% bridging fibrosis reported in French young adults or 6% in European young adult HCV patients coinfected with HIV, as estimated by FibroTest V R (Martín-Carbonero et al, 2009;Poynard et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…A French study of FibroTest (known as FibroSure in the US, is a patented biomarker test that uses the results of six blood serum tests to generate a score that is correlated with the degree of liver damage in people with a variety of liver disease) and elastography in 7463 normal subjects found that 2.8% had evidence of liver fibrosis. 14 In the ALDDeS study, around 14% of hazardous drinkers had a red traffic light. 15 The study considers their range of estimates for fibrosis of 8-20% is reasonable for a high-risk community group.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…1 Liver injury arises from a wide range of causes such as alcohol and drug abuse, viral hepatitis, medications and obesity that cause excessive accumulation of extracellular matrix proteins within the liver parenchyma leading to fibrosis and eventually cirrhosis. 2 Historically, the gold standard for determining the degree of fibrosis was liver biopsy; which can be painful, expensive, has a risk of haemorrhage and requires assessment by a pathologist.…”
Section: Introductionmentioning
confidence: 99%